Application of self-assessment to improve students' critical thinking ability in mathematics learning - Prawidi wisnu; Sigit Raharjo (International Journal of Progressive Mathematics Education, 2025)
Purpose: To evaluate the implementation of formative self-assessment in mathematics education and its specific contribution to junior high school students' critical thinking and metacognitive awareness.Design/methodology/approach: This qualitative case study involved 22 students from a private junior high school in Depok City. Empirical data were collected via in-depth interviews, classroom observations, and self-assessment rubrics, followed by thematic analysis.Findings: Self-assessment effectively compelled students to reflect on problem-solving strategies, identify computational errors, and enhance critical reasoning. Despite initial cognitive confusion, explicit teacher scaffolding and structured rubrics successfully cultivated reflective habits and stimulated internal dialogue regarding mathematical processes.Practical implications: Mathematics educators should integrate structured self-assessment rubrics alongside targeted feedback to transition students from mere answer-seekers to independent, process-oriented learners.Originality/value: This study bridges a prominent literature gap by mapping the internal mechanisms through which junior high students adopt self-assessment, establishing it as a sustainable catalyst for critical inquiry. Purpose: Mengevaluasi penerapan asesmen diri formatif dalam pembelajaran matematika dan kontribusinya terhadap keterampilan berpikir kritis serta kesadaran metakognitif siswa SMP.Design/methodology/approach: Studi kasus kualitatif ini melibatkan 22 siswa SMP swasta di Kota Depok. Data empiris dikumpulkan melalui wawancara mendalam, observasi kelas, dan rubrik asesmen diri, kemudian dianalisis secara tematik.Findings: Asesmen diri terbukti mendorong siswa merefleksikan strategi pemecahan masalah, mengenali kesalahan komputasi, dan meningkatkan nalar kritis. Meski awalnya siswa mengalami kebingungan kognitif, panduan guru dan rubrik terstruktur sangat efektif dalam membentuk kebiasaan reflektif serta memicu dialog internal terkait proses matematis.Practical implications: Guru matematika direkomendasikan untuk mengintegrasikan rubrik asesmen diri dan umpan balik spesifik guna mengubah orientasi siswa dari sekadar pencari jawaban akhir menjadi pembelajar mandiri yang berorientasi pada proses.Originality/value: Penelitian ini mengisi kesenjangan literatur dengan memetakan mekanisme internal siswa SMP dalam mengadopsi asesmen diri, mengukuhkannya sebagai katalis berkelanjutan bagi pembentukan pemikiran kritis.